The association between affective temperaments and depressive symptoms in a population of medical university students, Poland - Bartosik, Natalia Karina; Frankowski, Rafał; Kobierecki, Mateusz; Deska, Kacper; Twarowski, Aleksander; Bąk, Bartłomiej; Kosmalski, Marcin; Pietras, Tadeusz (Frontiers in Psychiatry, 2023)
Compared to their peers, medical students are more exposed to stress, and many present symptoms of depression, making them a group prone to experiencing mental illnesses. This study investigates a potential link between the occurrence of symptoms of depression and the dominating type of affective temperament in young people studying at a medical university. One hundred thirty-four medical students were surveyed using two validated questionnaires; the Polish versions of Beck's Depression Inventory-II (BDI-II) and the Temperament Evaluation of the Memphis, Pisa, and San Diego Autoquestionnaire (TEMPS-A). The data analysis revealed a significant link between symptoms of depression and affective temperaments, most significantly in subjects with a predominantly anxious temperament. This study confirms the role of various affective temperaments as a risk factor for mood disorders, specifically depression.